Thought Centers and their Impact on Public Policy Making in the Kurdistan Region (Critical Study) - Fattah, Omed Rafiq (Journal of University of Human Development, 2016)
Today, think tanks and research centers are the most important indictors to assess the state development and expect the possibilities for the future. According to academic and scientific perception, these think tanks offer scientific research and analysis for all the issues and problems facing the state. From this perspective, the think tanks deals with the causes of the problems, offer recommendations and solutions. This research is mainly an attempt to investigate the obstacles and opportunities of the think tanks in Kurdistan region. By doing this, we can determine the capability of Kurdistan in terms of research, and also we can inform the Kurdish decision makers in Kurdistan that in today's world the process of making decision is not related with the personal mood or personalization, but rational. For instance, the policy makers in the modern countries such as the United States, in their decisions and public policy largely depend on the recommendations and solutions that are given by think tanks, which is why the United States allocates large amounts of money for think